The Implementation of Law No: 24 of 2009, Concerning the Flag, Language, National Emblem and National Anthem for Students of SMPS 8 Alwashliyah - Zahara, Siti Fatimah; Putri, Jihan Hidayah; Prihatini, Syafrina (IJCS: International Journal of Community Service, 2024)
The community service program partners are students from Alwashliyah 8 Medan Middle School. The background is the law regarding the flag, language and national symbols, as well as the national anthem. The red and white flag, the Indonesian language Garuda Pancasila, and the national anthem Indonesia Raya are the national identity and identity of the unitary Republic of Indonesia. These four symbols are a reflection of the country's sovereignty in relations with other countries. The main target in this activity is the implementation of Law N0. 24 of 2009 for students at SMP Alwashliyah 8 Medan with the theme "Implementation of Law No: 24 of 2009 concerning the Flag, Language and National Emblem, and the National Anthem." The delivery method uses kahoot learning media and lectures conducted by lecturers and students of the Indonesian Language Education Study Program, FKIP, Alwashliyah University, Medan. The results achieved from this service program are (1) The unified state flag of the Republic of Indonesia, hereinafter referred to as the state flag, is the red and white. (2) The language used for generations by Indonesian citizens in areas within the territory of the unitary State of the Republic of Indonesia. (3) The symbol of the unitary state of the Republic of Indonesia, hereinafter referred to as the State Emblem, is the Garuda. Pancasila with the motto Bhinneka Tunggal Ika. and finally (4) Introducing in detail the national anthem. In this activity, students as partners were introduced to the implementation or implementation activities of Law no. 24 of 2009 Flag, Language and National Emblem, as well as the National Anthem (Indonesian national anthem).